Processing the past : - Francis X. Blouin Jr. and William G. Rosenberg. (Oxford University Press)
Authoritative history and authoritative archives -- The turn away from historical authority in the archives -- Archival authorities and new technologies -- The turn away from archival authority in history -- Archival essentialism and the archival divide -- The social memory problem -- Contested archives, contested sources -- The archivist as activist in the production of (historical) knowledge -- Rethinking archival politics : trust, truth, and the law -- Archives and the cyberinfrastructure -- Can archives and history reconnect : bridging the archival divide.